Responsible business : self-governance and law in transnational economic transactions - Dilling, Olaf; Herberg, Martin; Winter, Gerd (Oñati international series in law and society., 2008)
With the globalisation of markets, the phenomenon of market failure has also been globalised. This work includes a collection of empirical studies concerning self-regulation. Suitable for those interested in the sociological aspects of company and insolvency law, it features contributors who are experienced sociologists and public law scholars.